S anion modified ReB2 catalyst, preparation method and application of S anion modified ReB2 catalyst in hydrogen production by electrocatalytic water splitting with wide pH value

By using S anion modified ReB2 catalyst in electrocatalytic water cracking catalyst, the problem of limited application in a wide pH range environment is solved, and the performance of efficient electrocatalytic hydrogen evolution reaction under different pH conditions is achieved, and the catalyst is improved stability.

CN119465265AActive Publication Date: 2025-02-18NORTHEAST NORMAL UNIVERSITY
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411597263.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-11
Publication Date
2025-02-18
Estimated Expiration
2044-11-11

AI Technical Summary

Technical Problem

The existing electrocatalytic water cracking catalysts have limited applications in a wide pH range environment, which limits their practical application in complex water environments.

Method used

ReB2 catalyst modified with S anion is synthesized under relatively mild conditions through a molten salt-assisted preparation method to form a nanosheet-like structure. Doping sulfur regulates the electronic structure of the catalyst, making it excellent in electrolytes with different pH values. catalytic properties.

Benefits of technology

The S anion-modified ReB2 catalyst showed high-efficiency electrocatalytic hydrogen evolution reaction performance in three electrolytes with different pH values: 1.0M PBS, 0.5M H2SO4 and 1.0M KOH, and has long-term durability, which improves metal boronide in strong acids. Corrosion problems under alkaline conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119465265A_ABST
    Figure CN119465265A_ABST
Patent Text Reader

Abstract

The invention discloses an S anion modified ReB2 catalyst, a preparation method and application of the S anion modified ReB2 catalyst in hydrogen production through wide-pH-value electro-catalytic water splitting, and belongs to the technical field of catalyst synthesis and application of electro-catalytic water splitting. According to the molten salt assisted preparation method of the S anion modified ReB2 catalyst, the S anion doped diboride electrocatalyst (S-ReB2) is synthesized in one step under the relatively mild condition, the nano-sheet-shaped morphology is beneficial to exposure of more catalytic active sites, meanwhile, the electronic structure of metal Re in the catalyst is adjusted through doping of S, and the performance of the catalyst is improved. Therefore, the S-ReB2 has excellent catalytic performance on electro-catalytic hydrogen evolution reaction (HER) in electrolytes with different pH values. According to the S anion modified ReB2 catalyst prepared by the invention, the problem that the catalyst is extremely easy to corrode under the strong acid / alkali strong oxidation condition of metal boride is solved, and the energy conversion efficiency of converting electric energy into chemical energy is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of catalyst synthesis and electrocatalytic water splitting application, and specifically relates to a S anion-modified ReB2 catalyst, a preparation method and application thereof in electrocatalytic water splitting to produce hydrogen at a wide pH value. Background Art

[0002] The shortage of fossil fuels and environmental pollution are receiving widespread attention from countries around the world and have become the focus of research by many scholars. To solve this problem, the development of clean and efficient secondary energy is considered to be one of the feasible methods. Among many clean energy sources, hydrogen energy is considered to be one of the most promising clean energy sources due to its high energy density and zero carbon emissions. Compared with hydrogen produced from fossil fuels, the products of hydrogen production by water electrolysis technology are hydrogen and oxygen, without carbon dioxide and other toxic and harmful substances, and it is a green hydrogen production technology. However, the water splitting reaction is not easy to occur in thermodynamics and kinetics, and the energy consumption and cost of water electrolysis hydrogen production technology are relatively high. Therefore, it is necessary to develop efficient water splitting catalysts to improve the activity of electrodes, reduce the energy consumption of electrolyzers, thereby reducing the cost of water electrolysis and promoting its commercial application. Traditionally, Pt-based precious metals (such as Pt, Ru, Pd, Ir, etc.) have been considered the most ideal catalysts due to their high efficiency and excellent stability. However, the high cost and low crustal reserves of precious metals have greatly limited their widespread application and become the main obstacle to competing with traditional energy sources. Therefore, finding alternative cheap materials has become a new research focus to achieve a better balance between performance, cost and stability.

[0003] Transition metal borides have adjustable composition and structure and their unique bonding characteristics give them excellent physical and chemical properties, which have attracted widespread attention from researchers. Boron (B) is a metalloid element with an electronegativity between metals and non-metals. Boron atoms have an electron-deficient structure, and the number of its valence electrons is less than the number of valence orbitals. This electron-deficient feature allows boron atoms to exhibit a rich covalent bonding pattern in different boride lattices. The rich composition, structure and bonding characteristics give borides significant bulk properties such as superconductivity, superhardness, thermoelectricity, and surface catalytic properties for different chemical reactions. For example, Edward H.Sargent et al. reported a phase composition modulation method for preparing effective boride / borate-based catalysts. First, NiFe boride was synthesized and used as a template precursor to form an active NiFe borate catalyst. The boride-derived oxide was subjected to a 1M KOH electrolyte and a current density of 10 mA cm -2 The overpotential was 167 mV, and the overpotential was 1000 mA cm -2Zou Xiaoxin and others studied the high-temperature and high-pressure synthesis, structural analysis, and water splitting hydrogen properties of multiple α-MoB2, β-MoB2, MoB, and Mo2B. Among them, α-MoB2 containing a borane subunit structure showed the best catalytic performance under acidic conditions, and could obtain the 1000mAcm-2 expected in practical applications at a small overpotential (334mV). -2 These catalysts have good catalytic performance in either acidic or alkaline environments, but have limited applications in wide pH range environments, which severely restricts their practical applications in complex aqueous environments with different pH values. Therefore, designing electrocatalysts with good catalytic activity in a wide pH range medium is very important and remains a daunting challenge.

[0004] Anion doping regulation strategy has become one of the effective ways to improve the electrochemical performance of transition metal borides (TMBs). Heteroatom doping can effectively adjust the conductivity of the catalyst and cause the Fermi level of the catalyst to shift. By replacing atoms in the lattice with impurity atoms, excess electrons or holes can be introduced into the material. The electronic interaction between heteroatoms and metal borides changes the inherent electron transfer process, thereby changing the local charge distribution of the active site. Summary of the invention

[0005] The present invention aims to improve the utilization rate of energy conversion and promote the development of hydrogen economy, and proposes a S anion-modified ReB2 catalyst, a preparation method and its application in electrocatalytic water splitting to produce hydrogen under a wide pH value (wide pH means that the electrocatalytic hydrogen evolution reaction can be catalyzed under acidic, neutral and alkaline conditions).

[0006] The present invention proposes a molten salt-assisted preparation method for a S anion-modified ReB2 catalyst, which is to synthesize a S anion-doped diboride electrocatalyst (S-ReB2) in one step under relatively mild conditions. The nanosheet morphology is conducive to exposing more catalytic active sites. At the same time, the S doping adjusts the electronic structure of the metal Re in the catalyst, so that S-ReB2 exhibits excellent catalytic performance for the electrocatalytic hydrogen evolution reaction (HER) in electrolytes with different pH values. Specifically, in the three electrolytes of 1.0M PBS, 0.5M H2SO4 and 1.0M KOH, overpotentials of 144mV, 158mV and 139mV (1.0M KOH) are required, corresponding to 10mA cm -2 The invention enriches the application of boride catalysts in electrocatalytic hydrogen evolution reaction in wide pH electrolytes and provides the possibility of further improving the hydrogen evolution performance of boride catalysts.

[0007] The present invention discloses a method for preparing a S anion-modified ReB2 catalyst, which comprises the following steps: firstly, a rhenium source, a boron source and a sulfur source are uniformly mixed, and the mixture A is fully ground; then, sodium chloride and potassium chloride are uniformly mixed with the mixture A, and the mixture is fully ground again to obtain a mixture B; the mixture B is transferred into a tubular furnace and calcined at a high temperature in an Ar gas environment; after calcination, the temperature is cooled to room temperature, and the obtained product is placed in deionized water and stirred and washed thoroughly, and the obtained precipitate obtained after the supernatant is removed is washed with ethanol, the precipitate is collected by centrifugation, and the S anion-modified ReB2 catalyst is obtained after drying.

[0008] In the above method, the molar ratio of the rhenium source, the boron source and the sulfur source is 1:1-5:0.4-2;

[0009] The molar ratio of sodium chloride to potassium chloride is 1:1-2; the molar ratio of rhenium source to sodium chloride is 1:30-40;

[0010] In the above method, the high temperature calcination temperature is 650-1000°C, the high temperature calcination time is 0.5h-3h, and the heating rate during high temperature calcination is 3-6°C min -1 ;

[0011] In the above method, the product obtained by cooling to room temperature after calcination is placed in deionized water at 70 to 90°C and fully stirred and washed for 15 to 30 minutes;

[0012] In the above method, the sulfur source includes, but is not limited to, one or a mixture of organic sulfur-containing compounds such as sulfur powder, thiourea, thioacetamide, and mercaptans;

[0013] In the above method, the rhenium source includes but is not limited to one or a mixture of rhenium powder, rhenium dioxide, and ammonium rhenate;

[0014] In the above method, the boron source includes but is not limited to amorphous boron powder, sodium borohydride, boron trichloride or a mixture of the two or more thereof.

[0015] The S anion-modified ReB2 catalyst described in the present invention is prepared by the above method.

[0016] The S anion-modified ReB2 catalyst of the present invention can be used in the electrocatalytic water splitting hydrogen production under a wide pH value.

[0017] Compared with the prior art, the present invention has the following innovative features:

[0018] 1. The synthetic raw materials are cheap, the synthesis temperature is low, the synthesis method is novel, the controllability is high, and the sample properties have good reproducibility.

[0019] 2. The obtained S anion-modified ReB2 catalyst is an ultrathin nanosheet structure (length 600-700nm, thickness about 5nm). This ultrathin nanosheet greatly improves the electrochemical specific surface area and mass transfer efficiency of the obtained material.

[0020] 3. The obtained material is a new type of electrocatalytic water splitting catalyst. Sulfur doping adjusts the surface electronic structure of the catalyst, so that S-ReB2 exhibits enhanced electrochemical performance for HER in three electrolytes with different pH values: 1.0 M PBS, 0.5 M H2SO4 and 1.0 M KOH.

[0021] 4. The obtained S anion-modified ReB2 catalyst improves the problem that metal borides are easily corroded under strong acid / base oxidizing conditions, thereby improving the energy conversion efficiency of converting electrical energy into chemical energy. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 : XRD spectrum of the S-modified ReB2 catalyst (S-ReB2) prepared in Example 1;

[0023] Figure 2 : SEM image of the S-modified ReB2 catalyst (S-ReB2) prepared in Example 1;

[0024] Figure 3 : AFM image of the S-modified ReB2 catalyst (S-ReB2) prepared in Example 1;

[0025] Figure 4 : TEM and mapping images of the S-modified ReB2 catalyst (S-ReB2) prepared in Example 1; Figure 4 a is a TEM image of a single S-ReB2 nanosheet. Figure 4 b is the HRTEM image of S-ReB2. Figure 4 c~4f are STEM images of S-ReB2 and the existence and distribution of Re, B, and S in the nanosheets, respectively;

[0026] Figure 5 : Re 4f ( Figure 5 a) and B1s( Figure 5 b) XPS spectrum;

[0027] Figure 6 : The S-ReB2 catalyst (S-ReB2) prepared in Example 1 and ReB2, Re, Pt / C in 0.5M H2SO4 ( Figure 6 a), 1.0M PBS ( Figure 6 b), and 1.0 M KOH ( Figure 6 c) The hydrogen evolution reaction polarization curve;

[0028] Figure 7 : The S anion modified ReB2 catalyst (S-ReB2) prepared in Example 1 was heated to 0.5M H2SO4 ( Figure 7 a), 1.0M PBS ( Figure 7 b), and 1.0 M KOH ( Figure 7 c) Catalytic stability curve. DETAILED DESCRIPTION

[0029] The present invention will be further described below in conjunction with the accompanying drawings and embodiments, but the protection scope of the present invention is not limited to the following embodiments.

[0030] Example 1

[0031] (1) Weigh 0.001 mol of rhenium powder (Re) and 0.002 mol of amorphous boron powder (B), and then weigh 0.001 mol of sulfur powder (S), grind and mix them thoroughly to obtain a mixture A; 铼 :n 硼 :n 硫 =1:2:1;

[0032] (2) Mixture A was uniformly mixed with 2.014 g of sodium chloride (0.035 mol) and 2.570 g of potassium chloride (0.035 mol), and the mixture was thoroughly ground for 10 min to obtain mixture B;

[0033] (3) Mixture B was transferred into a tube furnace and heated to 1000°C in an Ar gas environment for 1 h at a heating rate of 5°C min -1 After the reaction, the temperature was cooled to room temperature, the sample was taken out and placed in 1000 mL of deionized water at 80°C, fully stirred and washed for 20 minutes, the supernatant was removed and the resulting precipitate was washed with ethanol, the precipitate was collected by centrifugation and then dried to obtain a S anion-modified ReB2 catalyst (product mass 0.18 g) with a molar ratio of metal rhenium to boron atoms of 1:2 (MB2), i.e., a metal boride water splitting catalyst.

[0034] The material prepared by the above method was subjected to the electrocatalytic water splitting HER property test in a standard three-electrode electrolytic cell: 3.5 mg of the catalyst powder prepared in step (3) of this embodiment was fully ground and dispersed in 100 μL of a mixed solution of perfluorosulfonic acid resin and isopropanol (the volume ratio was 1:10), and then 5 μL of the mixed solution was dropped on the surface of the glassy carbon electrode. After drying, a catalyst loading of 2.5 mg cm was obtained. -2The working electrode is 1.0M PBS (neutral), 0.5M H2SO4 (pH 0.3), or 1.0M KOH (pH 13.8) solution. Under alkaline conditions (i.e., the electrolyte is 1.0M KOH), the reference electrode is a mercury oxide electrode, and the counter electrode is a graphite carbon rod; under acidic and neutral conditions (i.e., the electrolyte is 1.0M PBS and 0.5MH2SO4), the counter electrode is a platinum wire, and the reference electrode is saturated silver chloride. It should be noted that all potentials obtained with mercury oxide and saturated silver chloride as reference electrodes in the electrocatalytic test are converted into reversible hydrogen electrode potentials in the property spectrum, and the external power supply is the main battery of the electrochemical workstation.

[0035] Some structural and performance studies were carried out on the materials prepared by the above method.

[0036] Figure 1 This is the XRD spectrum of the obtained material, which is well consistent with the hexagonal phase ReB2 (JCPDS No.73-1392). The results show that the metal diboride catalyst material is successfully prepared. Since the sulfur doping amount is very small, no characteristic diffraction peak related to sulfur is shown. Figure 2 This is a scanning electron microscope (SEM) image of the obtained material. The nanosheet structure of S-ReB2 stacked together after doping was observed by scanning electron microscopy. Figure 3 The AFM scan of the obtained material obtained by atomic force microscopy (the inset is the corresponding height distribution curve). The thickness of the S-ReB2 nanosheet is about 5nm; Figure 4 a is a transmission electron microscopy (TEM) image of the obtained material. The results show that the sheet structure array is composed of irregular hexagonal nanosheets with a size of 600-700nm, which is consistent with the SEM results. In more detail, high-resolution transmission electron microscopy (HRTEM) tests of S-ReB2 were carried out. Figure 4 In b, two sets of lattice fringes show interplanar spacings of 0.251 and 0.186 nm, which match well with the (100) and (004) planes of the hexagonal phase of S-ReB2, respectively. The composition of S-ReB2 was also analyzed by scanning transmission electron microscopy (STEM) combined with energy dispersive X-ray spectroscopy (EDS) to confirm the presence and distribution of different elements in a single nanosheet. Figure 4 The results from c~4f show that the Re, B, and S elements are evenly distributed throughout the nanosheet, further proving the successful incorporation of S and illustrating the successful preparation of sheet-structured S-ReB2 catalytic materials.

[0037] Figure 5 Re 4f( Figure 5 b) and B1s XPS( Figure 5b) Spectrum, it can be seen that the doping effect of S promotes electron transfer at the oxidized metal interface, exposing more catalytic active sites with high catalytic activity. Catalytic activity test:

[0038] Figure 6 In 0.5M H2SO4 ( Figure 6 a), 1.0M PBS ( Figure 6 b), and 1.0 M KOH ( Figure 6 c) The hydrogen evolution polarization curves measured by the three-electrode system of the electrochemical workstation under the conditions of overpotential of 158 mV, 144 mV, and 139 mV, respectively, and the current density reached 10 mA cm -2 , which is better than the catalytic performance of ReB2 and Re, and close to that of commercial Pt / C, indicating that the catalyst prepared by the present invention has a good hydrogen evolution effect.

[0039] Figure 7 In 0.5M H2SO4 ( Figure 7 a), 1.0M PBS ( Figure 7 b) and 1.0 M KOH ( Figure 7 c) under the condition of stability curve measured by three-electrode system of electrochemical workstation, the catalytic performance was almost not attenuated for more than 25 hours, indicating that the catalyst prepared by the present invention has good stability.

[0040] Example 2

[0041] Example 1 is basically the same, but it is necessary to pay attention to n 铼 :n 硼 :n 硫 =1:1:1, the product mass is 0.15g.

[0042] Electrocatalytic performance of the obtained samples: The hydrogen evolution polarization curves measured under the conditions of 1.0 M PBS, 0.5 M H2SO4, and 1.0 M KOH were 196 mV, 202 mV, and 184 mV, respectively, and the current density reached 10 mA cm -2 And after 25 hours of operation, its catalytic performance has hardly declined.

[0043] Example 3

[0044] Example 1 is basically the same, but it is necessary to pay attention to n 铼 :n 硼 :n 硫 =1:5:1, the product mass is 0.186g.

[0045] Electrocatalytic performance of the obtained samples: The hydrogen evolution polarization curves measured under the conditions of 1.0 M PBS, 0.5 M H2SO4, and 1.0 M KOH were 153 mV, 179 mV, and 166 mV, respectively, and the current density reached 10 mA cm -2 And after 15 hours of operation, its catalytic performance has hardly declined.

[0046] Example 4

[0047] Example 1 is basically the same, but it is necessary to pay attention to n 铼 :n 硼 :n 硫 =1:2:0.4, the product mass is 0.18g.

[0048] Electrocatalytic performance of the obtained samples: The hydrogen evolution polarization curves measured under the conditions of 1.0 M PBS, 0.5 M H2SO4, and 1.0 M KOH were 307 mV, 324 mV, and 377 mV, respectively, and the current density reached 10 mA cm -2 And after 35 hours of operation, its catalytic performance has almost no attenuation, which shows that the amount of sulfur doping has a certain influence on the catalyst performance.

[0049] Example 5

[0050] Example 1 is basically the same, but it is necessary to pay attention to n 铼 :n 硼 :n 硫 =1:2:2, the product mass is 0.19g.

[0051] Electrocatalytic performance of the obtained samples: The hydrogen evolution polarization curves measured under the conditions of 1.0 M PBS, 0.5 M H2SO4, and 1.0 M KOH were 149 mV, 162 mV, and 144 mV, respectively, and the current density reached 10 mA cm -2 And after 25 hours of operation, its catalytic performance has hardly declined.

[0052] Example 6

[0053] Example 1 is basically the same, except that it should be noted that the tubular furnace calcination temperature is 650° C. and the product mass is 0.18 g.

[0054] Electrocatalytic performance of the obtained samples: The hydrogen evolution polarization curves measured under the conditions of 1.0 M PBS, 0.5 M H2SO4, and 1.0 M KOH were 189 mV, 206 mV, and 214 mV, respectively, and the current density reached 10 mA cm -2 And after 30 hours of operation, its catalytic performance has hardly declined.

[0055] Example 7

[0056] Example 1 is basically the same, except that it should be noted that the calcination temperature in the tubular furnace is 800° C. and the product mass is 0.18 g.

[0057] Electrocatalytic performance of the obtained samples: The hydrogen evolution polarization curves measured under the conditions of 1.0 M PBS, 0.5 M H2SO4, and 1.0 M KOH were 155 mV, 179 mV, and 165 mV, respectively, and the current density reached 10 mA cm -2 And after 30 hours of operation, its catalytic performance has hardly declined.

[0058] Example 8

[0059] Example 1 is basically the same, except that the rhenium source is replaced with rhenium dioxide, and the product mass is 0.218 g.

[0060] Electrocatalytic performance of the obtained samples: The hydrogen evolution polarization curves measured under the conditions of 1.0 M PBS, 0.5 M H2SO4, and 1.0 M KOH were 147 mV, 159 mV, and 152 mV, respectively, and the current density reached 10 mA cm -2 And after 35 hours of operation, its catalytic performance has hardly declined.

[0061] Example 9

[0062] Example 1 is basically the same, except that the rhenium source is replaced with ammonium rhenate, and the mass of the product is 0.26 g.

[0063] Electrocatalytic performance of the obtained samples: The hydrogen evolution polarization curves measured under the conditions of 1.0 M PBS, 0.5 M H2SO4, and 1.0 M KOH were 142 mV, 164 mV, and 144 mV, respectively, and the current density reached 10 mA cm -2 And after 30 hours of operation, its catalytic performance has hardly declined.

[0064] Example 10

[0065] Example 1 is basically the same, except that the boron source is replaced with sodium borohydride, and the mass of the product is 0.18 g.

[0066] Electrocatalytic performance of the obtained samples: The hydrogen evolution polarization curves measured under the conditions of 1.0 M PBS, 0.5 M H2SO4, and 1.0 M KOH were 153 mV, 157 mV, and 164 mV, respectively, and the current density reached 10 mA cm -2 And after 30 hours of operation, its catalytic performance has hardly declined.

[0067] Example 11

[0068] Example 1 is basically the same, except that the boron source is replaced with boron trichloride and the mass of the product is 0.18 g.

[0069] Electrocatalytic performance of the obtained samples: The hydrogen evolution polarization curves measured under the conditions of 1.0 M PBS, 0.5 M H2SO4, and 1.0 M KOH were 141 mV, 155 mV, and 174 mV, respectively, and the current density reached 10 mA cm -2 And after 30 hours of operation, its catalytic performance has hardly declined.

[0070] Example 12

[0071] Example 1 is basically the same, except that the sulfur source is replaced with thiourea, and the mass of the product is 0.18 g.

[0072] Electrocatalytic performance of the obtained samples: The hydrogen evolution polarization curves measured under the conditions of 1.0 M PBS, 0.5 M H2SO4, and 1.0 M KOH were 147 mV, 159 mV, and 180 mV, respectively, and the current density reached 10 mA cm -2 And after 30 hours of operation, its catalytic performance has hardly declined.

[0073] Example 13

[0074] Example 1 is basically the same, except that the sulfur source is replaced with thioacetamide, and the mass of the product is 0.18 g.

[0075] Electrocatalytic performance of the obtained samples: The hydrogen evolution polarization curves measured under the conditions of 1.0 M PBS, 0.5 M H2SO4, and 1.0 M KOH were 162 mV, 179 mV, and 191 mV, respectively, and the current density reached 10 mA cm -2 And after 35 hours of operation, its catalytic performance has hardly declined.

[0076] The above-mentioned implementation modes are only preferred embodiments of the present invention, but the protection scope of the present invention is not limited thereto. Any changes, substitutions and improvements that can be easily thought of by technicians familiar with the technical field within the spirit and principles of the present invention should be covered within the protection scope of the present invention.

Claims

1. A method for preparing a S anion-modified ReB2 catalyst, characterized in that: First, the rhenium source, boron source and sulfur source are evenly mixed and fully ground to obtain a mixture A; then sodium chloride and potassium chloride are evenly mixed with the mixture A, and the mixture is fully ground again to obtain a mixture B; the mixture B is calcined at high temperature in an Ar gas environment; after calcination, it is cooled to room temperature, and the obtained product is placed in deionized water and stirred and washed thoroughly. After removing the supernatant, the obtained precipitate is washed with ethanol, the precipitate is collected by centrifugation, and the S anion-modified ReB2 catalyst is obtained after drying.

2. The method for preparing a S anion-modified ReB2 catalyst according to claim 1, characterized in that: The molar ratio of the rhenium source, the boron source and the sulfur source is 1:1-5:0.4-2; the molar ratio of the sodium chloride and the potassium chloride is 1:1-2; the molar ratio of the rhenium source and the sodium chloride is 1:30-40.

3. The method for preparing a S anion-modified ReB2 catalyst according to claim 1, characterized in that: The temperature of high temperature calcination is 650~1000℃, the time of high temperature calcination is 120~195min, and the heating rate during high temperature calcination is 3~6℃min -1 .

4. The method for preparing a S anion-modified ReB2 catalyst according to claim 1, characterized in that: The product obtained by cooling to room temperature after calcination is placed in deionized water at 70 to 90° C. and fully stirred and washed for 15 to 30 minutes.

5. The method for preparing a S anion-modified ReB2 catalyst according to claim 1, characterized in that: The sulfur source is one or a mixture of sulfur powder, thiourea, thioacetamide, and mercaptan; the rhenium source is one or a mixture of rhenium powder, rhenium dioxide, and ammonium rhenate; and the boron source is one or a mixture of amorphous boron powder, sodium borohydride, and boron trichloride.

6. A S anion-modified ReB2 catalyst, characterized in that: The invention is prepared by the preparation method according to any one of claims 1 to 5.

7. Use of the S anion-modified ReB2 catalyst according to claim 6 in electrocatalytic water splitting to produce hydrogen at a wide pH value.

Citation Information

Patent Citations

  • Nano transition metal boride catalyst and application thereof in electrocatalytic water cracking for hydrogen production

    CN109225195A

  • Mass production of metal borides by molten salt electrolysis

    EP4134352A1